Multiple drug resistant Vibrio cholerae, Salmonella and Shigella from Nepalgunj Cholera outbreak and different hospitals of Nepal - Shah, Binod Kumar; Sharma, Sapana; Shakya, Gita; Upadhyay, Bishnu Prasad (Nepalese Journal of Biosciences, 2013)
Diarrhoea is a major health problem throughout the world, and responsible for high morbidity and mortality in Nepal. The crosssectional prospective study was carried out to screen ESBL producer from MDR Vibrio Cholerae, Salmonella and Shigella from 268 diarrhoeal stools from Nepalgunj Cholera outbreak and different hospitals of Nepal during April 2010 to January 2011. The specimens were processed by standard microbiological methods and confirmed with serology. Altogether 14.18% of bacteria were isolated with 8.21% V. cholerae O1 El Tor Ogawa, 2.24% Shigella flexneri B and 3.73% Salmonella spp. Highest bacterial culture (47.36%) were isolated in Kathmandu while highest V. cholerae (77.27%) were isolated in Nepalgunj. The highest number of Salmonella spp. and Shigella spp. were isolated from Kanti Children’s Hospital. Highest bacteria isolation (47.36%) and highest V. cholerae isolation (81.81%) were observed in the August. The bacteria isolation was significantly associated with places and months (p<0.05). However, there was no statistical difference in the bacteria isolation with sex (P>0.05). 100% V. cholerae, 100% Shigella spp. and 80% Salmonella spp. were MDR while only one Salmonella Cholerasuis was found ESBL producer. DOI: http://dx.doi.org/10.3126/njbs.v2i0.7487 Nepalese Journal of Biosciences 2 : 31-39 (2012)